SUSCEPTIBILITY OF STRAWBERRY CULTIVARS TO Colletotrichum acutatum J.H. SIMMONDS - Anna Wagner; Beata Hetman (Acta Scientiarum Polonorum: Hortorum Cultus, 2016)
The investigations were carried out for three years with 8 strawberry cultivars grown in plastic tunnel. The plants were inoculated with the mixture of Colletotrichum acutatum isolates obtained from diseased plants of strawberry. All tested cultivars were susceptible to C. acutatum but in the different degree. The results showed that cv. ‘Camarosa’ was the most susceptible because of the highest disease index and the lowest yield of healthy fruit, while cv. ‘Senga Sengana’ was the most resistant. The results are important both for the producers and the breeders.